2015
DOI: 10.1039/c5ra13593a
|View full text |Cite
|
Sign up to set email alerts
|

Enantio- & chemo-selective preparation of enantiomerically enriched aliphatic nitro alcohols using Candida parapsilosis ATCC 7330

Abstract: The title biocatalyst mediates the asymmetric, chemoselective reduction of nitroketones wherein the keto group is preferred with respect to the nitro group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 67 publications
(82 reference statements)
0
4
0
Order By: Relevance
“…Even though cells harvested at 14 h produced the same ketone at less conversion (38%), these cells were used to visualise the site of biotransformation. For several other substrates reported earlier from our lab, the 14 h harvested cells produced the desired optically pure products with maximum ee (up to >99%) 1 2 3 6 7 26 29 30 33 34 35 .…”
Section: Resultsmentioning
confidence: 69%
“…Even though cells harvested at 14 h produced the same ketone at less conversion (38%), these cells were used to visualise the site of biotransformation. For several other substrates reported earlier from our lab, the 14 h harvested cells produced the desired optically pure products with maximum ee (up to >99%) 1 2 3 6 7 26 29 30 33 34 35 .…”
Section: Resultsmentioning
confidence: 69%
“…Lipase, esterase, halohydrin dehalogenase, and HNL catalyzed retro-Henry reaction are used in the kinetic resolution of a racemic β-nitroalcohol or an epoxide. [12][13][14][15][16] Alcohol dehydrogenase catalyzed asymmetric reduction, [17][18][19][20] and HNL catalyzed nitroaldol reaction [21][22][23][24][25] are the other two routes. Both kinetic resolution and asymmetric reduction requires an additional step of substrate preparation, while the former could provide a maximum 50% theoretical yield.…”
Section: Introductionmentioning
confidence: 99%
“…In 2008, Kroutil et al [25] reported on the conversion of 1-nitro-3-phenylpropan-2-one and 1-nitro-2-octanone into the enantiopure (S)-nitroalcohols in 47% and 75% yield, respectively, by using the lyophilized cells of Comomonas testoteroni. Recently [26], the whole cells of Candida parapsilosis ATCC 7330 were employed to catalyse the enantioselective reduction of some aliphatic derivatives 3 (only R = alkyl) in water with ethanol as a cosolvent, at room temperature, and in 4 h reaction time (conversion yields 54-76%, ee = 8.2-81%). The formation of the (R) or (S) enantiomer of the corresponding nitroalcohol depended upon the nature of the R group.…”
Section: Synthesis Of Nitroketones 3 and Biocatalysed Reduction To Dementioning
confidence: 99%